Deaf Student and Mental Act in Mathematics Problem Solving - La Ode Amril; Darhim; Dadang Juandi (Universitas Djuanda, 2020)
Mathematics has an important role in the cognitive development of deaf students. Through learning mathematics in schools, deaf students will explore and build knowledge, because literally mathematics is the parent of knowledge and human activities. One important aspect in learning mathematics is the ability to solve problems. Problem solving means engaging in a task for which the solution method is not known in advance. In order to find a solution, students must draw on their knowledge, and through this process, they will often develop new mathematical understandings.This study aims to analyze the mental act of deaf students in solving mathematical problems in fraction material. Respondents of 20 students were randomly selected from 3 special schools. This type of research is qualitative with a case study design. Data was collected through the instrument of problem solving abilities, interviews, and observations. Data were analyzed using grouded theory. The results of this study indicate that the mental act used by deaf students in solving mathematical problems is interpreting, explaining, inferring, and problem solving.